Selected Abstracts of the 20th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 23-26, 2024 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2025)
Selected Abstracts of the 20th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 23rd-26th, 2024 CHILDREN’S HEALTH: MESSAGES FROM THE FUTURE The Workshop has been organized with the patronage of Autonomous Region of Sardinia, City of Cagliari, Azienda Ospedaliera di Cagliari, University of Cagliari, Board of Physicians of the Province of Cagliari, Italian-Albanian Pediatric Society, AMBO (Alleanza per un Ambiente a misura di Bambino: alliance for a child-friendly environment), European Project Better4u, European Project Life Milch, National Confederation of Pediatrics Heads (CONAPP), Italian Federation of Family Pediatricians (FIMP), Italian-Arabian Pediatric Society (IAPS), Italian-Romanian Pediatric Society (IRPS), Norman Group of Neonatal and Pediatric Nephrology, International Academy of Perinatal Medicine, Italian Society of Pediatric Allergology and Immunology (SIAIP), Italian Society of Clinical Biochemistry (SIBioC), Italian Society of Gynecology of Infancy and Adolescence (SIGIA), Italian Society of Neonatology (SIN), Italian Society of Hospital Pediatricians (SIPO), Association SIPO in the World, Italian Society of Developmental Origins of Health and Disease (SI-DOHaD), Alfred Nobel International Study Center Sanremo, Italian Society of Pediatricians (SIMPE), Italian Society of Pediatric Psychology (S.I.P.Ped.), Romanian Society of Pediatrics, Italian Society for Research on Essential Oils (SIROE), Italian Society of Neonatal Nursing (SIN INF), Union of European Neonatal and Perinatal Societies (UENPS). ABS 1. EXAMINATION OF CBD PRODUCT SAFETY MESSAGING FOR CHILDREN IN SOCIAL MEDIA PLATFORMS: A COMPARATIVE STUDY • I. Ham, O.S. Khilji, M. Leiner (El Paso, Texas, USA) ABS 2. L1CAM IS SECRETED THROUGH EXOSOMES IN THE DEVELOPING HUMAN BRAIN • F. Cau, F. Coghe, G. Faa (Cagliari, Italy; Philadelphia, Pennsylvania, USA) ABS 3. LANGUAGE DEFICIENCIES IN CHILDHOOD – INTERDISCIPLINARY APPROACHES • S.L. Burlea, G. Burlea, V.V. Lupu (Iași, Romania) ABS 4. LONG-TERM EFFECTS OF EARLY VOCAL CONTACT, BY PARENTS’ BOOK-READING, FOR PRETERM NEWBORNS IN NICUs • C. Peila, S. Deantoni, L. Riboldi, M. Mainardi, E. Bertino, A. Coscia (Turin, Italy) ABS 5. RESPIRATORY DISTRESS IN A FEMALE INFANT WITH PRIMARY CILIARY DYSKINESIA. A CASE REPORT • E. Tsianaka, M. Karypidou, A. Loutsidi, K. Angelou, A. Charitou (Athens, Greece) ABS 6. WHEN CLINICAL FINDINGS REVEAL THE DIAGNOSIS: A CASE OF WILLIAMS SYNDROME • E. Esposito, G. Sanna, F. Comisi, M. Marica, S. Savasta (Cagliari, Italy) ABS 7. NON-FATAL DROWNING: A CASE REPORT • V. Carosio, C. Cocco, R. Basile, G. Cherchi (Cagliari, Italy) ABS 8. CLEIDOCRANIAL DYSPLASIA • B.M. Trapani (Sion, Switzerland) ABS 9. PANAYIOTOPOULOS SYNDROME: A CASE REPORT • L. Calandriello, V. Ferasin, S. Bellonzi, L. Dell’Anna, C. Lorenzetto, F. Marino, G. Passarella, F. Rigon, E. Fiumana, A. Mussari, L. Saggioro, F. Sansone, S. Rugolotto (Rovigo, Padua and Verona, Italy) ABS 10. MEASURING KNOWLEDGE OF PARENTS AND CHILDREN WITH CONGENITAL HEART DISEASE: ADAPTATION AND VALIDATION OF THE “LEUVEN KNOWLEDGE QUESTIONNAIRE FOR CONGENITAL HEART DISEASE” • S. Flocco, F. Crò, C. Arrigoni, G. Conte, G. Zaffino, S. De Vecchi, L. Schianchi, G. Campioni, M. Chessa, R. Caruso, A. Magon (Milan and Pavia, Italy) ABS 11. NEW PERSPECTIVES ON NEONATAL LUNG ASSESSMENT • S. Carnazzo, S. Nasikas, F.F. Comisi (Catania, Italy; Paris, France) ABS 12. THE ODYSSEY OF CHRONIC PAIN • G. Sanna, F.F. Comisi, E. Esposito, C. Soddu, S. Savasta (Cagliari, Italy) ABS 13. PROPHYLAXIS IN CHILDHOOD IN THE REPUBLIC OF BULGARIA • T. Itova (Ruse, Bulgaria) ABS 14. LYSOZYME IS HIGHLY EXPRESSED IN MATERNAL MILK STEM/PROGENITOR CELLS • G. Faa, G. Pichiri, P. Coni, M. Piras, Y. Gibo, A. Reali, V. Fanos (Cagliari, Italy; Philadelphia, Pennsylvania, USA; Matsumoto, Japan) ABS 15. TRIMETHYLAMINURIA • B.M. Trapani (Sion, Switzerland) ABS 16. STEVENS-JOHNSON SYNDROME IN CHILDHOOD: TWO CASE REPORTS • F. Marino, L. Dell’Anna, V. Ferasin, F. Rigon, S. Bellonzi, L. Calandriello, F. Sansone, C. Lorenzetto, E. Fiumana, G. Passarella, A. Mussari, L. Saggioro, S. Rugolotto (Rovigo, Padua and Verona, Italy) ABS 17. KAWASAKI DISEASE OR MIS-C? • S. Vendemmia, I. Pezone, M. Vendemmia (Aversa and Naples, Italy) ABS 18. RISK FACTORS FOR RECOARCTATION OF THE AORTA AFTER SURGICAL REPAIR IN PEDIATRIC PATIENTS • G. Concas, E. Esposito, A. Atzei, P. Neroni, A. Giamberti, M. Chessa, V. Fanos (Cagliari and Milan, Italy) ABS 19. PRIMARY LYMPHEDEMA: TWO CASE REPORTS IN CHILDREN • L. Dell’Anna, F. Marino, F. Rigon, S. Bellonzi, E. Fiumana, L. Calandriello, F. Sansone, C. Lorenzetto, G. Passarella, V. Ferasin, L. Saggioro, A. Mussari, C. Bertolin, S. Rugolotto (Padua, Rovigo and Verona, Italy) ABS 20. A COMMON PRESENTATION, YET A RARE DIAGNOSIS: INSIGHTS INTO MRFACD SYNDROME • F.F. Comisi, E. Esposito, G. Sanna, M. Marica, C. Soddu, S. Savasta (Cagliari, Italy) ABS 21. ADMINISTERING DRUGS IN NEONATAL POPULATION THROUGH IN-LINE FILTERS: RESULTS OF FILTERABILITY STUDIES • C. Capetti, E. Maggiora, M. Capitanio, S. Deantoni, C. Quarti, C.G. Catona, F. De Matteis, S. Cosimi, M. Luciano, E. Bertino, A. Coscia, F. Cresi (Turin and Milan, Italy) ABS 22. A RETROSPECTIVE ANALYSIS OF UPJO CLINICAL BURDEN IN SARDINIAN CHILDREN • A. Bertini, M. Cossu, M.E. Murru, M. Gamberoni, V. Manca, E. Flore, F. Zurrida, G. Masnata (Cagliari, Italy) ABS 23. CLINICAL VARIABILITY IN SSADHD • M. Gamberoni, C. Sbaffi, G. Sanna, M. Asunis, M. Balzarini, E. Flore, D. Pruna, G. Masnata (Cagliari, Italy) ABS 24. AN UNSUPERVISED LEARNING TOOL FOR STEM CELL BURDEN ASSESSMENT IN THE PRETERM KIDNEY • M. Fraschini, V. Fanos, L. Didaci, G. Faa (Cagliari, Italy; Philadelphia, Pennsylvania, USA) ABS 25. MOVEMENT-DEPENDENT MODULATION OF MULTISENSORY INTEGRATION EARLY IN LIFE: THE DEVELOPMENTAL CONTEXT OF A SPATIAL BODILY-SELF REPRESENTATION • C. Peila, S. Deantoni, L. Riboldi, G. Serra, A. Rossi Sebastiano, I. Ronga, K. Poles, S. Russo, A. Comanducci, A. Coscia, E. Bertino, A. Pigorini, F. Garbarini (Turin and Milan, Italy) ABS 26. BASIC FAMILY-CENTERED CESAREAN SECTION OUTCOMES: A RETROSPECTIVE COHORT STUDY • L. Saggioro, F. Marino, L. Dell’Anna, V. Ferasin, F. Rigon, S. Bellonzi, L. Calandriello, F. Sansone, C. Lorenzetto, E. Fiumana, G. Passarella, A. Mussari, S. Rugolotto (Verona, Rovigo and Padua, Italy) ABS 27. FEBRILE SEIZURES AS A MANIFESTATION OF ENCEPHALITIS • M. Cossu, M. Olla, A. Falchi, A. Ghigino, A. Bertini, S. Cossu, D. Pruna, B. Cancedda, M. Tiddia, G. Masnata, M. Zanda (Cagliari, Italy) ABS 28. ASSESSING EARLY PREDICTORS OF 12-MONTH NEURODEVELOPMENT IN INFANTS WITH CONGENITAL CMV: A SINGLE-CENTER EXPERIENCE • C. Deantoni, A. Spadavecchia, C. Rubino, A. Leone, C. Terzi, C. Angieri, E. Maggiora, C. Peila, E. Bertino, F. Cresi, A. Coscia (Turin, Italy) ABS 29. CASE REPORT: INFANT WITH PNEUMOCOCCAL MENINGITIS AND SEPSIS • A. Falchi, A. Ghigino, V. Sanneris, C. Sbaffi, D. Manunza, D. Congiu, G. Masnata, M. Zanda (Cagliari, Italy) ABS 30. UNMASKING THE OVERLOOKED: RECOGNIZING BEALS-HECHT SYNDROME • G. Sanna, E. Esposito, F.F. Comisi, C. Soddu, S. Savasta (Cagliari, Italy) ABS 31. RENAL INVOLVEMENT IN TWO PEDIATRIC CASES OF SEPSIS • F. Zanco, V. Sanneris, M. Cossu, M. Olla, F. Zurrida, V. Manca, M. Balzarini, L. Foschini, M. Zanda, G. Masnata (Cagliari, Italy) ABS 32. BASSEL-HAGEN DISEASE AND ARTHRALGIA: IS THE EXT GENE TO BLAME? • F.F. Comisi, C. Cerruto, E. Esposito, G. Sanna, S. Carnazzo, S. Savasta, R. Mura (Cagliari, Vittoria and Catania, Italy) ABS 33. A CAT-ASTROPHIC CASE OF FUO! • E. Esposito, F. Comisi, G. Sanna, S. Campus, S. Savasta (Cagliari, Italy) ABS 34. NON-OBSTETRIC SURGERY DURING PREGNANCY: A CASE REPORT AND A NEONATOLOGY PERSPECTIVE • V. Ferasin, S. Bellonzi, L. Calandriello, L. Dell’Anna, C. Lorenzetto, F. Marino, G. Passarella, F. Rigon, E. Fiumana, A. Mussari, L. Saggioro, F. Sansone, S. Rugolotto (Padua and Rovigo, Italy) ABS 35. BODY DYSMORPHIC DISORDER: SOCIAL MEDIA IMPACT • S. Petza (Cagliari, Italy) ABS 36. BROWN RECLUSE SPIDER BITE IN CHILDREN: A CASE REPORT • M. Rossi, G. Pianese, M.R. Angelo, G. Cherchi (Cagliari, Italy) ABS 37. NIGHT AND DAY URINARY INCONTINENCE • A. Bertini, M. Cossu, M. Gamberoni, V. Manca, E. Flore, F. Zurrida, G. Masnata (Cagliari, Italy) ABS 38. SEGMENTAL PIK3CA-RELATED OVERGROWTH SYNDROME: DIAGNOSIS AND NEW THERAPEUTIC STRATEGIES • C. Sbaffi, M. Gamberoni, M. Manca, E. Flore, V. Setzu, S. Murru, M. Balzarini, G. Masnata (Cagliari, Italy) ABS 39. MISSING A PINCH OF SALT IN A NEONATE • F. Sansone, V. Ferasin, S. Bellonzi, L. Dell’Anna, C. Lorenzetto, F. Marino, G. Passarella, F. Rigon, E. Fiumana, A. Mussari, L. Saggioro, L. Calandriello, S. Rugolotto (Rovigo, Padua and Verona, Italy) ABS 40. SYDENHAM’S CHOREA: CORTICOSTEROIDS’ ROLE IN QUICK SYMPTOM CONTROL • M. Manca, G. Sanna, F. Zanco, V. Sanneris, S. Cossu, S. Dettori, D. Pruna, E. Flore, C. Angioni, S. Marras, M. Zanda, G. Masnata (Cagliari, Italy) ABS 41. A NEW CHALLENGE: BITTER TASTE RECEPTORS • B.M. Trapani, G. Trapani (Sion, Switzerland; Sanremo, Italy) ABS 42. FETAL AND NEONATAL ARRYTHMIAS: PERSONAL EXPERIENCE WITH 167 CASES • M.R. Scanu, A. Atzei, P. Neroni, V. Fanos (Cagliari, Italy) ABS 43. NOT JUST HYPERGLICINEMIA… • I. Rulli, A.M. Carcione, E. Gitto (Messina, Italy) ABS 44. EXTERNAL CEPHALOHEMATOMA WITH ATYPICAL CLINICAL COURSE • A. D’Apuzzo, M. Vendemmia (Naples, Italy) ABS 45. ATP: A POTENTIAL WEAPON AGAINST HCAI IN THE NICU • G. Simoni, M. Melis, V. Fanos (Cagliari, Italy) ABS 46. MAGNET INGESTION IN CHILDREN: A CASE REPORT • M. Marsan, M. Brutti, R. Cacace, G. Amato, F. Sau, G. Cherchi (Cagliari, Italy) ABS 47. INTERNATIONAL STANDARDS FOR TWIN NEWBORN WEIGHT, LENGTH, AND HEAD CIRCUMFERENCE BY GESTATIONAL AGE AND SEX: THE INTERGROWTH-21ST CROSS-SECTIONAL STUDY • F. Giuliani, S. Deantoni, S. Gandino, A. Coscia, I. Stura, S.H. Kennedy, A.T. Papageorghiou, E. Bertino, G. Migliaretti, J. Villar for the International Fetal and Newborn Growth Consortium (INTERGROWTH-21st) (Turin, Italy; Oxford, UK) ABS 48. ACUTE LYMPHOBLASTIC LEUKEMIA AND GANGLIONEUROBLASTOMA: CASE REPORT • F. Gigliotti, C. Fortugno, E. Galea, R. Cantaffa, D. Loiacono, V. Talarico, M. Ceravolo, A. Pugliese, G. Raiola, M.C. Galati (Catanzaro, Italy) ABS 49. ANTITUMOR ACTIVITY OF LAROTRECTINIB IN GLIOBLASTOMA MULTIFORME WITH NTRK GENE AMPLIFICATION CASE REPORT • F. Gigliotti, C. Fortugno, E. Galea, R. Cantaffa, R.L. Fabiano, V. Talarico, M. Ceravolo, G. Raiola, M.C. Galati (Catanzaro, Italy) ABS 50. ABERNETHY TYPE II MALFORMATION IN CHILDREN: AN UNUSUAL PRESENTATION. A CASE OF ABERNETHY MALFORMATION • V. Talarico, A. Nicoletti, G. Guarascio, A. Viscomi, G. Stranieri, A. Gigliotti, M.C. Galati, D. Alberti, G. Raiola (Catanzaro and Brescia, Italy) ABS 51. A STUDY OF CORD BLOOD ALKALINE PHOSPHATASE AS A PREDICTOR OF NEONATAL HYPERBILIRUBINEMIA IN A TERTIARY HOSPITAL • V.B. Sonawane, R. Agarwal, M. Maksud, A. Saxena, V. Kotrashetti (Nerul, Maharashtra, India) ABS 52. PERCEIVED FAMILY FUNCTION, PERCEIVED SOCIAL SUPPORT AND DEPRESSION OF NEW PARENTS UNDER COVID-19 PANDEMIC: A DYADIC ANALYSIS • T. Kokkinaki, K. Koutra, O. Michopoulou, L. Chaziraki, P. Kokarida, E. Hatzidaki (Rethymnon, Heraklion and Chania, Greece) ABS 53. EVALUATING THE PREVALENCE OF POSTNATAL GROWTH FALTERING OF PRETERM INFANTS USING TWO GROWTH CHARTS AND ITS RELATION TO CLINICAL AND NUTRITIONAL PARAMETERS • I. Kakatsaki, N. Anagnostatou, T. Roumeliotaki, S. Papanikolaou, E. Hatzidaki (Heraklion, Greece)